Henry VII's London in the Great Chronicle - Boffey, Julia (Book collections on Project MUSE., 2019)
"This modernized extract from The Great Chronicle of London covers the reign of England's first Tudor king, Henry VII (1485-1509). It gives an eye-witness account of events in London, and of news from elsewhere, from the viewpoint of a well-to- do citizen who was closely involved in civic administration. It describes many notable public events: riots and uprisings, executions, coronations, royal marriages and funerals, and ceremonial activities involving the mayor and aldermen. Its year by year entries also cover matters like the weather, the cost of living, taxes, and the effects of building work undertaken in the city. Although its compiler worked to a scheme common to other London chronicles from the period, he was ready to express his own views on a number of matters, and wrote with keen observation and occasional wit"--